Research on Manufacturing Composite Materials on the Basis of PLA/Talc in Application of 3D Printing Technology - Lê Thiên Đỉnh,; Vũ Tiến Trung,; Phạm Huy Lâm,; Nguyễn Ngọc Thư,; Lê Minh Thành,; Lê Thanh Huy,; Hà Thúc Chí Nhân, (Journal of Technical Education Science, 2025)
This study aims to fabricate a biodegradable composite material based on Polylactic acid (PLA) and Talc powder, then evaluate the impact of the PLA-g-MAH compatibilizer (MAH) on the properties of the material. The influence of Talc powder and MAH on PLA is characterized through mechanical properties, melt flow index (MFI), thermal properties, and morphology of the material. The results show that the structure and properties of the PLA/Talc mixture differ from those of PLA/Talc/MAH and pure PLA. The presence of PLA-g-MAH (MAH) enhances the flexural strength, impact strength, and tensile strength of pure PLA. Through DSC analysis, we found that the glass transition temperature (Tg) increased, and the cold crystallization temperature (Tc) decreased when Talc and PLA-g-MAH (MAH) were blended into PLA compared to pure PLA. TGA analysis showed that the addition of Talc reduced the thermal stability of PLA, and decomposition occurred at a lower temperature as the Talc content increased. SEM images of the material indicated that Talc flakes were fairly evenly distributed in the polymer matrix without significant aggregation. In addition, the biodegradable composite material PLA/Talc/MAH was studied by increasing the Talc content in the mixture, contributing to improving tensile strength, hardness and dimensional stability due to the ability to limit the movement of polymer chains in the PLA matrix. The results showed that the PLA/Talc/MAH mixture with 10% Talc by weight exhibited a higher melt flow index (MFI) than pure PLA, and the mechanical properties of this mixture were sufficient to produce 3D filaments.